THE DIGITAL MARKETING TO INFLUENCE CUSTOMER SATISFACTION MEDIATED BY PURCHASE DECISION - Bachri, Syamsul; Putra, Setiawan Mandala; Farid, Erwan Sastrawan; Darman, Darman; Mayapada, Arung Gihna (Universitas Brawijaya, Indonesia, 2023)
Consumer satisfaction and purchasing decisions made by consumers have always been a concern of marketers, taking into account these two aspects can encourage businesses to develop. Digital marketing is one of the factors that can shape consumer satisfaction and purchase decisions. For this reason, this study aims to prove whether there is an influence between digital marketing on purchasing decisions and consumer satisfaction, the influence of purchasing decisions on consumer satisfaction, and to prove whether purchasing decisions can mediate the relationship between digital marketing and customer satisfaction. This study, using Structural Equation Modeling (SEM) Partial Least Squares (PLS) analysis to test the hypothesis. This study also using a non-probability sampling method through a judgmental sampling technique. The minimum number of samples in using SEM is 100-200 samples, and this study uses a sample of 100 respondents. The results of the study show that digital marketing influences purchasing decisions and also influences consumer satisfaction. Other findings show that purchasing decisions have a positive effect on consumer satisfaction. The research findings also show that purchasing decisions can positively mediate the relationship between digital marketing and consumer satisfaction. The findings of this study have practical implications especially transformations in digital-based marketing strategies. The use of various digital marketing strategies such as email marketing, search engine optimization, search engine marketing, content marketing, social media marketing, etc., can help companies or marketers to increase consumer decisions in making purchases which at the last can build their satisfaction.